The potential of electricity generation using wind turbine system in Malaysia - 271840 Goh, En Ling; Hasimah Abd. Rahman, supervisor; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2007